2021
DOI: 10.1016/j.hlc.2020.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in the Care of Familial Hypercholesterolaemia in Australia: First Report From the National Registry

Abstract: Background Familial hypercholesterolaemia (FH) is under-diagnosed and under-treated worldwide, including Australia. National registries play a key role in identifying patients with FH, understanding gaps in care and advancing the science of FH to improve care for these patients. Methods The FH Australasia Network has established a national web-based registry to raise awareness of the condition, facilitate service planning and inform best practice and care services in Australia. We conducted a cross-sectional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…A steering committee, selected from board members of the FH Australasia Registry Network [5] , appointed a writing group and invited contributions from diverse clinical specialties and health consumers [4] . The protocols followed are detailed elsewhere [4] .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A steering committee, selected from board members of the FH Australasia Registry Network [5] , appointed a writing group and invited contributions from diverse clinical specialties and health consumers [4] . The protocols followed are detailed elsewhere [4] .…”
Section: Methodsmentioning
confidence: 99%
“…[CoR Strong; LoE Moderate] Statins and other systemically absorbed cholesterol lowering drugs should be discontinued 3 months before conception, as well as during pregnancy and breastfeeding [ 1 , 3 , 7 ]. [CoR Strong; LoE Moderate] In women with homozygous FH and clinical ASCVD, use of statins and ezetimibe may be considered after the first trimester [ 1 , 5 , 36 ]. [CoR Weak; LoE Moderate] Although CACS may be useful for initial risk stratification of asymptomatic patients prior to commencing a statin, it should not be used to monitor the efficacy of therapy [ 1 , 15 , 16 , 46 ].…”
Section: Key Evidenced-based Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we are proposing that, based on individual considerations, clinicians treating COVID-19 patients initiate/continue or even intensify statin treatment in the context of stroke prevention in FH patients and also in other patients with severe hypercholesterolemia. This recommendation is highly relevant against the background that a significant fraction of FH patients uses statins either irregularly, at too low a dose, or not at all [ [17] , [18] , [19] ]. So, clinicians need to take care that hospitalized FH patients with COVID-19 reach the treatment goals for LDL-C, which usually requires a high-efficiency combined lipid-lowering therapy that includes a high dose of a high-intensity statin.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that effective statin therapy is of utmost importance among FH patients to effectively lower serum LDL-C and to improve endothelial function. Unfortunately, even diagnosed FH patients are often treated with ineffective statin dosages [8] . Additionally, it has been reported that among hospitalized patients with COVID-19 statin treatment is in very many cases discontinued.…”
mentioning
confidence: 99%